Modelling Theway Berbantu Media Audio Visual dalam Meningkatkan Minat Belajar Pendidikan Agama Islam - Syaikhul Lubib Agustian, Muhammad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
The focus of this article is the implementation of the use of modelling theway method assisted by audio-visual media in increasing interest in learning Islamic religious education at SMPN 1 Kalidawir. This research method is qualitative research with data collection methods of interviews, observation and documentation. Analysis is descriptive. The results of this study indicate that: First, the use of modelling theway method assisted by audio-visual media has been implemented gradually, because the existing facilities in school partners are still constrained by the ability of educators who do not understand how to operate it. Second, the implementation also has a good effect on the ability of students to understand learning materials. Thirdly, the implication of using this method is that students are more confident in explaining the material that has been obtained, and the understanding of the material is also very good so that there is an increase in learning evaluation.